Analysis of Recruitment and Selection in Improving Employee Performance in Elyogroup Medan - Sofiah, Ella; Lubis, Kartika Sari (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Human resources are the main asset for an organization who are active planners and actors in various activities within the organization. The success of an organization is supported by good employee performance. To get employees with quality performance, effective recruitment is needed. The formulation in this study is how the recruitment process and selection process are carried out by Elyogroup. The method used is a descriptive qualitative method with observation data collection methods and unstructured interviews. Data collection used a purposive sampling method by selecting business owners as informants to obtain information used to complete this research. The results of this study are that Elyogroup recruitment is still placing job vacancy advertisements using Instagram social media. The selection process was carried out using file selection and structured and unstructured interviews.